Analyse von Benutzeranforderungen von Service-Kompositionen mittels Modelchecking - Nickel, Tobias

Towards Modeling Reconfiguration in Hierarchical Component Architectures - Becker, Steffen; Heinzemann, Christian; Priesterjahn, Claudia (Proceedings of the 15th ACM SigSoft International Symposium on Component-Based Software Engineering (CBSE))
Today's real-time embedded systems operate in frequently changing environments on which they react by self-adaptations. Such an approach needs adequate modeling support of these reconfigurations to enable verification of safety properties, e.g., by timed model checking. Component-based development of such systems realizes these self-adaptations by structural reconfigurations of components and their connectors. However, component models proposed in literature do not support reconfigurable components in real-time embedded context but focus on other domains like business information systems. In this paper, we present an extension of our modeling language MechatronicUML to support structural reconfigurations taking the specific requirements of our domain into account. Based on the proposed extension we outline our research roadmap to achieve verification and realization of systems modeled in MechatronicUML.

Model-Driven Performance Engineering of Self-Adaptive Systems: A Survey - Becker, Matthias; Luckey, Markus; Becker, Steffen (Proceedings of the 8th ACM SigSoft International Conference on Quality of Software Architectures (QoSA'12))
To meet quality-of-service requirements in changing environments, modern software systems adapt themselves. The structure, and correspondingly the behavior, of these systems undergoes continuous change. Model-driven performance engineering, however, assumes static system structures, behavior, and deployment. Hence, self-adaptive systems pose new challenges to model-driven performance engineering. There are a few surveys on self-adaptive systems, performance engineering, and the combination of both in the literature. In contrast to existing work, here we focus on model-driven performance analysis approaches. Based on a systematic literature review, we present a classication, identify open issues, and outline further research.

Generating Prototypes of Adaptive Component-based Software Systems for Performance Analysis - Mohr, Mario

Empirischer, quantitativer Vergleich von Modelltransformationssprachen - Lehrig, Sebastian

Weaving-based configuration and modular transformation of multi-layer systems - Besova, Galina; Walther, Sven; Wehrheim, Heike; Becker, Steffen (Proceedings of the 15th International Conference on Model Driven Engineering Languages & Systems (MoDELS))
In model-driven development of multi-layer systems (e.g. application, platform and infrastructure), each layer is usually described by separate models. When generating analysis models or code, these separate models rst of all need to be linked. Hence, existing model transformations for single layers cannot be simply re-used. In this paper, we present a modular approach to the transformation of multi-layer systems. It employs model weaving to dene the interconnections between models of dierent layers. The weaving models themselves are subject to model transformations: The result of transforming a weaving model constitutes a conguration for the models obtained by transforming single layers, thereby allowing for a re-use of existing model transformations. We exemplify our approach by the generation of analysis models for component-based software.

Selected papers on Integrated Formal Methods (iFM09) - Leuschel, Michael; Wehrheim, Heike (Science of Computer Programming)

Reputation-based Reliability Prediction of Service Compositions - Besova, Galina; Wehrheim, Heike; Wagner, Annika (Electronic Notes in Theoretical Computer Science)
Today, the concept of service oriented architectures provides a way of building integrated solutions out of existing services. To this end, services from different providers are composed using advanced orchestration and choreography techniques. However, while this principle allows for greater flexibility at a smaller cost, the use of third party services also includes a risk: Deployed services might not work as claimed by their providers. In this paper, we propose a technique for analyzing the expected reliability of service compositions based on ratings given by (previous) service users. Every service thereby comes with a reputation, and the analysis computes an overall reliability of a service composition from the reputations of its constituent services. The proposed model-driven approach proceeds by translating statechart models of service compositions into input for a probabilistic model checker (PRISM) using state-of-the-art model transformations techniques. The approach has been implemented as an Eclipse plug-in and is fully compliant with UML.

Performance Prototyping with ProtoCom in a Virtualised Environment: A Case Study - Lehrig, Sebastian; Zolynski, Thomas (Proceedings of the Palladio Days 2011)
Performance prototyping is an often used technique to assess the performance of software architectures early in the development process without relying on models of the system under study. ProtoCom is a prototype generator for the PCM realised as model-2-text transformation for which no experience report in a larger, virtualised setting exists. In this paper, we report on four case studies performed with an improved version of ProtoCom and report on the results gained with respect to analysis accuracy and usability. Our results demonstrate that the new version is much easier to use than previous versions and that results gained in our virtualised execution environment help in early assessments of performance under realistic conditions.

Modellgetriebene Skalierbarkeitsanalyse von selbst-adaptiven Komponentenbasierten Softwaresystemen in der Cloud - Meyer, Joachim